WHO ARE THE INTELLECTUALS: A MODERNIST AND POSTMODERNIST DISCURSIVE PERSPECTIVE (Heritage, 2025)
Defining the position and importance of intellectuals in contemporary societies is one of the most important issues concerning its functioning. Accordingly, the paper deals, on the one hand, with the characteristics and social roles of intellectuals in modernist and postmodernist times and contexts. On the other hand, intellectuals are analyzed as an autonomous class, class dependent or non-class phenomenon. The discussion begins with a distinction between Western and Eastern concepts of intelligentsia, and defining the concept of paresis as essential for understanding the discourses/metanarratives of intellectuals. Postamental attributes of modernist and postmodernist intellectuals are necessarily connected with the general characteristics of the projects of modernity and postmodernity and with the original social, narrative, discursive, crisis and cultural characteristics of the time, i.e. the context, in which their engagement takes place, develops, and maintains. The paper ends by identifying essential premises for the analysis of Serbian intellectuals.
Keywords: intellectuals, intelligentsia, modern intellectuals, postmodern intellectuals, social criticism.